2014
DOI: 10.1002/2013je004585
|View full text |Cite
|
Sign up to set email alerts
|

Modeling VIRTIS/VEX O2(a1∆g) nightglow profiles affected by the propagation of gravity waves in the Venus upper mesosphere

Abstract: In this work we describe a model of the perturbation of the O 2 (a 1 Δ g ) nightglow limb profiles by the action of gravity waves (GWs) propagating in the Venus' upper atmosphere. Data have been acquired by the Visible and InfraRed Thermal Imaging Spectrometer (VIRTIS) on board the European Space Agency mission Venus Express (VEX). The high variability observed in the shape of the O 2 (a 1 Δ g ) nightglow limb profiles between 80 and 120 km, often characterized by the presence of a double peak, suggests the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The VeRa Radio Science Experiment also provides wave information that is extracted from temperature fluctuations . Lastly, current efforts are focusing upon characterizing gravity waves from VIRTIS observations of O 2 IR nightglow (Altieri et al 2014).…”
Section: Gravity Waves: Airglow and Other Signaturesmentioning
confidence: 99%
“…The VeRa Radio Science Experiment also provides wave information that is extracted from temperature fluctuations . Lastly, current efforts are focusing upon characterizing gravity waves from VIRTIS observations of O 2 IR nightglow (Altieri et al 2014).…”
Section: Gravity Waves: Airglow and Other Signaturesmentioning
confidence: 99%
“…In thermosphere (>110 km) a subsolar‐to‐antisolar (SS‐AS) circulation cell is driven by the solar heating (Sánchez‐Lavega et al, ). Thus, the dynamics in the transition region might be influenced by both of these modes (Bougher et al, ; Lellouch et al, ), as well as other mechanisms, such as gravity waves (Alexander, ; Altieri et al, ; Bertaux et al, ; Peralta et al, ; Zhang et al, ) and thermal tides (Zasova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…From limb mode observations O 2 (a 1 Δ g ) emission vertical profiles were obtained, and the mean altitude of the emission peak was found at 97.4 ± 2.5 km altitude. The double peak, observed in some cases, was interpreted after modeling (Altieri et al, 2014) as gravity waves with vertical wavelength of 10-14 km and horizontal wavelength of 100-1,000 km. The nadir measurements showed the distribution of the emission over the nightside and appearance of the local maxima at different latitudes and local time (LT), but on the averaged map, a wide spread spot of higher intensity of nightglow appeared around midnight (Piccioni et al, 2009;Shakun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The original method of identifying wave events and reconstructing IGW characteristics in planetary atmospheres we developed [Gubenko et al, 2008b[Gubenko et al, , 2011[Gubenko et al, , 2016a has been widely recognized by scientific community both in Russia and abroad. It is now being successfully used to study wave processes in the atmospheres of Earth [Horinouchi, Tsuda, 2009;Xiao, Hu, 2010;Rechou et al, 2014;Sacha et al, 2014;Noersomadi, Tsuda, 2017;Zagar et al, 2017] and Venus [Altieri et al, 2014;Peralta et al, 2015]. For example, Rechou et al [2014] have shown that numerical simulation data and analysis of independent radar and probe measurements in Earth's atmosphere demonstrate high efficiency of our method and high reliability of scientific results it yields.…”
Section: Introductionmentioning
confidence: 99%